Radium-223 inhibits osseous prostate cancer growth by dual targeting of cancer cells and bone microenvironment in mouse models - Suominen, Mari I. (Clin Cancer Res, 2017)
PURPOSE: Radium-223 dichloride (radium-223, Xofigo®), a targeted alpha therapy, is currently used for the treatment of patients with castration-resistant prostate cancer (CRPC) with bone metastases. This study examines the mode-of-action and antitumor efficacy of radium-223 in two prostate cancer xenograft models. EXPERIMENTAL DESIGN: Mice bearing intratibial LNCaP or LuCaP 58 tumors were randomized to groups (n = 12–17) based on lesion grade and/or serum PSA level and administered with radium-223 (300 kBq/kg) or vehicle, twice at 4-week intervals. X-rays and serum samples were obtained biweekly. Soft tissue tumors were observed macroscopically at sacrifice. Tibiae were analyzed by gamma counter, micro-CT, autoradiography and histology. RESULTS: Radium-223 inhibited tumor-induced osteoblastic bone growth and protected normal bone architecture leading to reduced bone volume in LNCaP and abiraterone-resistant LuCaP 58 models. Furthermore, radium-223 resulted in lower PSA values and reduced total tissue and tumor areas, indicating that treatment constrains prostate cancer growth in bone. In addition, radium-223 suppressed abnormal bone metabolic activity as evidenced by decreased number of osteoblasts and osteoclasts and reduced level of the bone formation marker PINP. Mode-of-action studies revealed that radium-223 was deposited in the intratumoral bone matrix. DNA double-strand breaks were induced in cancer cells within 24 hours after radium-223 treatment and PSA levels were significantly lower 72 hours post treatment providing further evidence of the anti-tumor effects. CONCLUSION: Taken together, radium-223 therapy exhibits a dual targeting mode-of-action that induces tumor cell death and suppresses tumor-induced pathological bone formation in tumor microenvironment in osseous CRPC growth in mice.